Horton Multisphere at Dow Chemical Company plant - Dow Chemical Company (1951)
General view of the Horton Multisphere storage tank at the Dow Chemical Company plant located in Freeport, Texas.
Keywords: Industries; Dow Chemical Company; Storage tanks